2017
DOI: 10.1007/s00259-017-3779-0
|View full text |Cite
|
Sign up to set email alerts
|

Elevated tumor-to-liver uptake ratio (TLR) from 18F–FDG-PET/CT predicts poor prognosis in stage IIA colorectal cancer following curative resection

Abstract: PurposeThe prognostic value of the tumor-to-liver uptake ratio (TLR) from 18-fluoro-2-deoxyglucose positron emission tomography/computed tomography (18F–FDG-PET/CT) in the early stage of colorectal cancer (CRC) is unclear. Notably, some stage IIA CRC patients experience early recurrence even after curative resection and might benefit from neoadjuvant or adjuvant chemotherapy. This study aims to evaluate whether elevated TLR from 18F–FDG-PET/CT can predict poor prognosis in stage IIA CRC patients undergoing cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 50 publications
1
29
1
Order By: Relevance
“…We also hypothesized that the combination of these metabolic criteria with the standard CRS risk 17,19,20 It has been shown in various cancers that high FDG uptake is associated with poorer prognosis. 21,23 In colorectal cancer and in CRLM, the prognostic value of 18 FDG-PET/CT has also been demonstrated, but its value in association with a clinical score has not yet been explored. 20,[24][25][26][27][28] We first observed that individual preoperative clinicopathological factors, CRS scores, and high-and low-risk CRS were not significantly different between patients who had the opposite postoperative oncological outcomes, confirming the poor prognostic accuracy of traditional clinical surrogates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also hypothesized that the combination of these metabolic criteria with the standard CRS risk 17,19,20 It has been shown in various cancers that high FDG uptake is associated with poorer prognosis. 21,23 In colorectal cancer and in CRLM, the prognostic value of 18 FDG-PET/CT has also been demonstrated, but its value in association with a clinical score has not yet been explored. 20,[24][25][26][27][28] We first observed that individual preoperative clinicopathological factors, CRS scores, and high-and low-risk CRS were not significantly different between patients who had the opposite postoperative oncological outcomes, confirming the poor prognostic accuracy of traditional clinical surrogates.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] The predictive and prognostic value of metabolic parameters derived from preoperative 18 FDG-PET/CT has already been demonstrated in several cancers including lung, esophageal, and colorectal neoplasms. [21][22][23] In CRLM, several studies have also demonstrated the prognostic value of the metabolic parameters measured during preoperative 18 FDG-PET/CT. 20,[24][25][26][27][28] In the present study, we analyzed whether baseline 18 FDG-PET/ CT metabolic characteristics of CRLM may serve to discriminate between patients who will obtain a significant oncological benefit from surgery and those who will not.…”
Section: Introductionmentioning
confidence: 99%
“…So far, in oncological PET, especially the tumour to liver ratio (TLR) has been used (one example of this approach is the work of Huang et al [7]). More recently, we have proposed the imagederived tumour to arterial blood standard uptake ratio (SUR) as a promising alternative [8,9] and investigated its properties and performance compared to SUV [5,10,11].…”
Section: Methodological Aspects Of Quantificationmentioning
confidence: 99%
“…Nevertheless, we can discriminate tumour viability from the immune reaction that will control the tumour or even destroy it. Actually, the intensity of the immune reaction might be a prognostic marker as suggested by Huang et al and others [7,15].…”
Section: Biological Aspectsmentioning
confidence: 99%
“…Some studies have demonstrated that conventional PET-derived parameters, such as maximum standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG), carry their own significance in stratifying survival of patients with CRC [5][6][7][8]. However, other studies yielded equivocal results [9,10]. The prognostic impact of those conventional PET-based parameters was not evident for patients with CRC, and the National Comprehensive Cancer Network guidelines recommended that 18 F-FDG-PET or PET/CT should be used selectively for potentially surgically curable metastatic diseases or should only be used to evaluate an equivocal finding on a contrastenhanced CT or MRI [11].…”
Section: Introductionmentioning
confidence: 99%